A gallbladder tumor revealing metastatic clear cell renal carcinoma: report of case and review of literature - Ghaouti Merieme; Znati Kaoutar; Jahid Ahmed; Zouaidia Fouad; Bernoussi Zakiya; Fakir Youssef El; Mahassini Najat (BMC, 2013)
Abstract Metastatic renal cell carcinoma in the gallbladder is extremely rare, with reported frequencies of less than 0.6% in large autopsy reviews. Only 40 cases were reported in the literature. We report a first case of gallbladder polypoid tumor revealing metastatic clear cell renal cell carcinoma, which demonstrates the importance of radiological tests, histology and immunohistochemistry when making a definitive diagnosis. These examinations also allow differentiating metastatic clear cell renal cell carcinoma from other polypoid lesions in the gallbladder with clear cell morphology. Cholecystectomy should be performed to obtain a definitive diagnosis and to improve survival in case of solitary metastatic renal cell carcinoma. Virtual slides The virtual slides' for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/8956897238238989